Human mesenchymal factors induce rat hippocampal‐ and human neural stem cell dependent oligodendrogenesis. Issue 1 (22nd September 2017) - Jadasz, Janusz J.; Tepe, Lena; Beyer, Felix; Samper Agrelo, Iria; Akkermann, Rainer; Spitzhorn, Lucas‐Sebastian; Silva, Maria Elena; Oreffo, Richard O. C.; Hartung, Hans‐Peter; Prigione, Alessandro; Rivera, Francisco J.; Adjaye, James; et al.
Abstract: The generation of new oligodendrocytes is essential for adult brain repair in diseases such as multiple sclerosis. We previously identified the multifunctional p57kip2 protein as a negative regulator of myelinating glial cell differentiation and as an intrinsic switch of glial fate decision in adult neural stem cells (aNSCs). In oligodendroglial precursor cells (OPCs), p57kip2 protein nuclear exclusion was recently found to be rate limiting for differentiation to proceed. Furthermore, stimulation with mesenchymal stem cell (MSC)‐derived factors enhanced oligodendrogenesis by yet unknown mechanisms. To elucidate this instructive interaction, we investigated to what degree MSC secreted factors are species dependent, whether hippocampal aNSCs respond equally well to such stimuli, whether apart from oligodendroglial differentiation also tissue integration and axonal wrapping can be promoted and whether the oligodendrogenic effect involved subcellular translocation of p57kip2. We found that CC1 positive oligodendrocytes within the hilus express nuclear p57kip2 protein and that MSC dependent stimulation of cultured hippocampal aNSCs was not accompanied by nuclear p57kip2 exclusion as observed for parenchymal OPCs after spontaneous differentiation. Stimulation with human MSC factors was observed to equally promote rat stem cell oligodendrogenesis, axonal wrapping and tissue integration. As forced nuclear shuttling of p57kip2 led to decreased CNPase‐ but elevated GFAP expression levels, this indicates heterogenic oligodendroglial mechanisms occurring between OPCs and aNSCs. We also show for the first time that dominant pro‐oligodendroglial factors derived from human fetal MSCs can instruct human induced pluripotent stem cell‐derived NSCs to differentiate into O4 positive oligodendrocytes. Main Points: Human fetal MSCs potently instruct oligodendrogenesis from adult rat hippocampal‐ and hIPSC‐ derived neural stem cells. Oligodendrocyte generation does not depend on nuclear p57kip2 protein shuttling as opposed to parenchymal OPC differentiation.